2019
DOI: 10.3390/su11102755
|View full text |Cite
|
Sign up to set email alerts
|

Internationalization Business Models and Patterns of SMEs and MNEs: A Qualitative Multi-Case Study in the Agrifood Sector

Abstract: Small- and Medium-sized Enterprises (SMEs) and Multinational Enterprises (MNEs) in the agri-food sector have been overcoming internationalization barriers. However, research is scarce, specifically to meet the Sustainable Development Goals, despite the importance of the sector. The main aim of our study is to explore the archetypes and internationalization pace of internationalized SMEs and MNEs in the agri-food sector, adopting an external perspective and an empirical approach. More particularly, the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 114 publications
(235 reference statements)
0
9
0
2
Order By: Relevance
“…The relationship between the internationalization model and macs Some studies (Cumming et al, 2017;Puck & Filatotchev, 2020) have related the ip to the study of corporate finance and strategic management. Following this line of research, we relate the ip with the macs, since accounting literature has given increased attention to the relationship between management accounting systems and strategy (Bedford et al, 2016;Bisbe & Malagueño, 2012;Davila et al, 2015;Franco-Santos et al, 2012;García-Álvarez et al, 2019;Gimbert et al, 2010;Gomez-Conde & Lopez-Valeiras, 2018;Gomez-Conde et al, 2019;Langfield-Smith, 2006;Lin et al, 2017;Lopez-Valeiras et al, 2015;Ramon-Jeronimo et al, 2019). This literature has focused on different strategic frameworks, such as strategy process (Mintzberg & Waters, 1985) and strategy typologies (Miles & Snow, 1978).…”
Section: Contabilidad Y Finanzasmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between the internationalization model and macs Some studies (Cumming et al, 2017;Puck & Filatotchev, 2020) have related the ip to the study of corporate finance and strategic management. Following this line of research, we relate the ip with the macs, since accounting literature has given increased attention to the relationship between management accounting systems and strategy (Bedford et al, 2016;Bisbe & Malagueño, 2012;Davila et al, 2015;Franco-Santos et al, 2012;García-Álvarez et al, 2019;Gimbert et al, 2010;Gomez-Conde & Lopez-Valeiras, 2018;Gomez-Conde et al, 2019;Langfield-Smith, 2006;Lin et al, 2017;Lopez-Valeiras et al, 2015;Ramon-Jeronimo et al, 2019). This literature has focused on different strategic frameworks, such as strategy process (Mintzberg & Waters, 1985) and strategy typologies (Miles & Snow, 1978).…”
Section: Contabilidad Y Finanzasmentioning
confidence: 99%
“…Despite the growing interest in the macs-strategy relationship (Bisbe & Malagueño, 2012;Franco-Santos et al, 2012;García-Álvarez et al, 2019;Gimbert et al, 2010;Gomez-Conde & Lopez-Valeiras, 2018;Gomez-Conde et al, 2019;Lopez-Valeiras et al, 2015;Ramon-Jeronimo et al, 2019), the picture presented in the literature was found to be fragmented (Langfield-Smith, 1997) with an inconsistent conceptualization and operationalization (Otley, 2016;Tucker et al, 2009). Some authors consider that there is little knowledge about the effects of macs in the strategy implementation (Coller et al, 2018;Frigotto et al, 2013;Skaerbaek & Tryggestad, 2010).…”
Section: Contabilidad Y Finanzas Introductionmentioning
confidence: 99%
“…In the perspective of one belt, one road, there was a need to integrate the concept of internationalization of Chinese firms and associated challenges in terms of developing internal brand equity. Based on this gap in previous studies suggested by García Álvarez de Perea et al (2019) , the following research tried to signify the internationalization challenges associated with one belt, one road initiative at the organizational level of Chinese firms. Moreover, the mediating role of brand knowledge dissemination toward developing employer-based brand equity was not studied before, and to overcome this gap, it was suggested by Zulkepli et al (2015) to evaluate the mediating role of brand knowledge dissemination which could lead to the development of EBBE.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the positive impact of eco-innovation on firms' financial performance (Marcus 2015) through results such as cost reductions and an increase of sales has been observed (Ociepa-Kubicka and Pachura 2017). Internationalisation and development of eco-innovations may bring economic growth to companies and improve their competitive advantage, however, it may give rise to uncertainties and are assumed to be risky processes (de Perea et al 2019). The development of new products or processes implies a high level of risk and paradoxically this type of risk can exert a negative impact on companies' internationalisation (Martínez-Román et al 2019).…”
Section: Introductionmentioning
confidence: 99%